Acoustic emission monitoring of a soil slope: Comparisons with continuous deformation measurements. Issue 4 (6th October 2014) - Smith, A.; Dixon, N.; Meldrum, P.; Haslam, E.; Chambers, J.
Abstract : Acoustic emission (AE) has become an established approach to monitor the stability of soil slopes. However, the challenge has been to develop strategies to interpret and quantify deformation behaviour from the measured AE. This paper presents the first comparison of continuous AE (measured using an active waveguide) and continuous subsurface deformation measurements. The active waveguide is installed in a borehole through a slope and comprises a metal waveguide rod or tube with a granular backfill surround. When the host slope deforms, the column of granular backfill also deforms, generating AE that can propagate along the waveguide. This paper presents results from a field trial at a reactivated soil slope in North Yorkshire, UK. The measurements confirm that AE rates generated are directly proportional to the velocity of slope movement (e.g. the AE rate versus velocity relationship determined for a series of slope movement events produced an R 2 value of 0·8) and demonstrate the performance of AE monitoring of active waveguides to provide continuous information on slope displacements and displacement rates with high temporal resolution.